Relative Bioavailability of Orally Dispersible Tablet Formulations of Levo‐ and Racemic Praziquantel: Two Phase I Studies - Wilhelmina Maria Bagchus; Deon Bezuidenhout; Eleanor Harrison‐Moench; Elly Kourany‐Lefoll; Peter Wolna; Oezkan Yalkinoglu (Wiley, 2019)
Orally dispersible tablet (ODT) formulations of levo praziquantel (L‐PZQ) and racemic PZQ (rac‐PZQ) are being developed to treat schistosomiasis in preschool‐aged children. Two crossover studies (N = 32 and 36, respectively) assessed the relative bioavailability of these ODTs vs. Cysticide in adults. Bioavailability for L‐PZQ of ODT rac‐PZQ and Cysticide at 40 mg/kg was comparable (L‐PZQ area under the concentration‐time curve from zero to infinity (AUC0-∞) test/reference ratio (90% confidence interval (CI)): 96% (84-111%)), whereas relative bioavailability of ODT L‐PZQ 20 mg/kg was ~40% that of Cysticide 40 mg/kg (test/reference: 40% (35-46%)). AUC0‐∞ and peak plasma concentration (Cmax) were highly variable in both studies. For both ODTs, L‐PZQ AUC0-∞ showed greater than dose‐proportional increase over the ranges tested and a significant food effect. Safety was comparable among formulations. The lower bioavailability of ODT L‐PZQ, as well as the high variability and nondose‐proportionality of pharmacokinetic (PK) parameters, highlighted the need for a dedicated pediatric dose‐finding study for the selection of the most appropriate formulation and dose (L‐PZQ ODT or rac‐PZQ ODT).